Exponential Consensus for Nonlinear Multi‐Agent Systems with Communication and Input Delays via Hybrid Control. Issue 4 (8th September 2017) - Wang, Yangling; Cao, Jinde; Wang, Haijun; Alsaedi, Ahmed; Alsaadi, Fuad E.
Abstract: This paper aims to investigate the exponential leader‐following consensus for nonlinear multi‐agent systems with time‐varying communication and input delays by using hybrid control. Based on the Lyapunov functional method, impulsive differential equation theory and matrix analysis, we show that all the followers can achieve leader‐following consensus with the virtual leader exponentially even if only a fraction of followers can obtain the leader's information. Two classes of exponential consensus criteria as well as the convergence rates for the controlled multi‐agent systems are presented under very relaxed interaction topology conditions, i.e., the directed interaction topology among the followers is only required to have p ( p >1) disjoint strong components. Finally, two numerical examples are given to validate the proposed theoretical results.